Household Schooling Decisions in Rural Pakistan - Sawada, Yasayuki; Lokshin, Michael (World Bank, Washington, DC, 2013)
Human capital investments in Pakistan are performing poorly; school enrollment is low, the high school dropout rate is high, and there is a definite gender gap in education. The authors conducted field surveys in 25 Pakistani villages and integrated their field observations, economic theory, and econometric analysis to investigate the sequential nature of education decisions--because current outcomes depend not only on current decisions but also on past decisions. Their full-information maximum likelihood estimate of the sequential schooling decision model reveals important dynamics affecting the gender gap in education, the effects of transitory income and wealth, and intrahousehold resource allocation patterns. They find, among other things, that in rural Pakistan: 1) There is a high educational retention rate, conditional on school entry, and that male and female schooling progression rates become comparable at higher levels of education. 2) A household's human and physical assets and changes in its income significantly affect children's education patterns. Birth order affects siblings' competition for resources. 3) Serious supply-side constraints on village girls' primary education suggest the importance of supply-side policy interventions in Pakistan's rural primary education--for example, providing more girls' primary schools close to villages and employing more female teachers.